Quantifying sedimentary ’blue carbon’ in relation to canopy cover in the seagrass meadows of Turneffe Atoll, Belize - Stacey L. Felgate; Richard Sanders; Valdemar Andrade; Christopher D. G. Barry; Hannah Brittain; Stephen Carpenter; Abel Carrias; Eliceo Cobb; Chris D. Evans; James Hunt; Anna Lichtschlag; Daniel J. Mayor; et al. (Frontiers in Marine Science, 2024)
Introduction Seagrass sediments are important ‘blue carbon’ reservoirs which store climatically significant quantities of organic carbon (C org ) at the global scale. Seagrass meadows that overly these sediments also provide a range of critical ecosystem services including shoreline stabilization, storm surge protection, and fisheries nursery grounds. However, the controls over accumulation and the sources of organic C to these sediments beds are highly variable and poorly understood with the relative importance of hydrodynamic setting, species composition and canopy density being unclear. Methods Here we address these questions using the first observation-based estimates of C org stocks and provenance on Turneffe Atoll, Belize, made via remotely-sensed habitat extent, local C org data and isotopic data. Sedimentary C org was highest in sediments underlying the most sheltered meadows and decreased with increasing exposure to wind and wave energy with the seagrass meadows in the central lagoon containing an extensive deposit of mangrove derived organic carbon, stabilized and protected by the overlying seagrass meadow. Results The influence of species composition appeared weak with the ubiquitous species T. testudinum occurring across a wide range of hydrodynamic regimes ranging from the most sheltered to the most energetic and being associated with a wide range of sedimentary organic C concentrations. Importantly from the perspective of remote sensing, org C concentrations were unrelated to canopy density. We hypothesize that this decoupling of organic C concentration from seagrass canopy cover reflects a much longer timescale for carbon storage in the sediments than the lifespan of the seagrass plants themselves and/or a substantial non seagrass derived organic C burden in seagrass sediments. Overall, we conservatively estimate that the top 30cm of sediments underlying the seagrass meadows overlying carbonate sediments on the atoll exterior store 0.58 x 10 6 Mg C org , most of which is seagrass-derived, whilst the sediments underlying the meadows within the central lagoon store an additional 1.28 x 10 6 Mg C org . When the maximum possible extent of seagrass is considered, this estimate increases to 3.54 x 10 6 Mg C org. Substantial C org stocks extending >1m depth were observed across all sites, and so these inventories are considered conservative. Discussion A preliminary ‘cost of loss’ for sedimentary C org in the top 30 cm of Turneffe Atoll’s seagrass meadows, based on a carbon trading value of €60 tCO 2 (eq), is estimated at €42 million for the outer atoll, increasing to €136 million when the mangrove-derived sediments of the central atoll are considered and €260 million when turbid areas are assumed to contain seagrass.

Corrigendum to ‘Factors influencing microplastic abundances in the sediments of a seagrass-dominated tropical atoll’ Environmental Pollution (2024) 357, 124483 - Freya Radford; Alice A. Horton; Stacey Felgate; Anna Lichtschlag; James Hunt; Valdemar Andrade; Richard Sanders; Claire Evans (Environmental Pollution, 2024)

Factors influencing microplastic abundances in the sediments of a seagrass-dominated tropical atoll - Freya Radford; Alice A. Horton; Stacey Felgate; Anna Lichtschlag; James Hunt; Valdemar Andrade; Richard Sanders; Claire Evans (Environmental Pollution, 2024)

Riverine concentrations and export of dissolved silicon, and potential controls on nutrient stoichiometry, across the land–ocean continuum in Great Britain - Andrew M. Tye; Helen P. Jarvie; Bryan M. Spears; Nancy B. Dise; Jennifer L. Williamson; Dan J. Lapworth; Don Monteith; Richard Sanders; Daniel J. Mayor; Michael J. Bowes; Michael Bowes; Annette Burden; et al. (Journal of Hydrology, 2024)

Marine nutrient subsidies promote biogeochemical hotspots in undisturbed, highly humic estuaries - Chris D. Evans; Stacey L. Felgate; Steffi Carter; Mark Stinchcombe; Edward Mawji; Andrew P. Rees; Inma Lebron; Richard Sanders; Paul Brickle; Daniel J. Mayor (Limnology and Oceanography, 2023)
The land‐ocean dissolved organic carbon (DOC) flux represents a significant term within the global carbon budget, with peatland‐dominated regions representing the most intense sources of terrestrial DOC export. As the interface between freshwater and marine systems, estuaries have the potential to act as a filter of the land‐ocean carbon flux, removing terrestrially derived DOC, which is present at low concentrations in the oceans, via a combination of physicochemical and biological processes. However, the fate of peat‐derived DOC within estuaries remains poorly quantified, partly due to the complicating influences of heterogeneous soils, land‐use, point sources, and upstream modification of organic matter. To minimize these modifying factors, we studied DOC and inorganic nutrients in four small, peat‐dominated, minimally disturbed, and oligotrophic Falkland Island estuaries. Contrary to expectations, we found limited evidence of physicochemical estuarine DOC removal, and instead observed apparent “hot zones” of biogeochemical activity, where terrestrially‐derived silicate mixed with inorganic nitrogen and phosphorus entering the estuaries from the nutrient‐rich marine ecosystem. In two estuaries, this coincided with apparent in situ DOC production. We suggest that the observed phenomena of marine nutrient subsidy of estuarine productivity, and flexible utilization of multiple nutrients within the oligotrophic system, may once have been widespread in temperate estuaries. However, this function has been lost in many ecosystems due to catchment eutrophication by agricultural and urban development. We conclude that the estuaries of the Falkland Islands provide a valuable pre‐disturbance analogue for natural biogeochemical functioning in temperate estuaries receiving high organic matter inputs.

Corrigendum: Effect of COVID-19 Anthropause on Water Clarity in the Belize Coastal Lagoon - Ileana A. Callejas; Christine M. Lee; Deepak R. Mishra; Stacey L. Felgate; Claire Evans; Abel Carrias; Andria Rosado; Robert Griffin; Emil A. Cherrington; Mariam Ayad; Megha Rudresh; Benjamin P. Page; et al. (Frontiers in Marine Science, 2021)

Effect of COVID-19 Anthropause on Water Clarity in the Belize Coastal Lagoon - Ileana A. Callejas; Christine M. Lee; Deepak R. Mishra; Stacey L. Felgate; Claire Evans; Abel Carrias; Andria Rosado; Robert Griffin; Emil A. Cherrington; Mariam Ayad; Megha Rudresh; Benjamin P. Page; et al. (Frontiers in Marine Science, 2021)
The Coronavirus disease 2019 (COVID-19) pandemic halted human activities globally in multiple sectors including tourism. As a result, nations with heavy tourism, such as Belize, experienced improvements in water quality. Remote sensing technologies can detect impacts of “anthropauses” on coastal water quality. In this study, moderate resolution imaging spectroradiometer (MODIS) satellite data were employed along the Belizean coast to investigate impacts of the COVID-19 shutdown on water quality. The attenuation coefficient at 490 nm, K d (490), was used as an indicator of water quality, with a lower K d (490) indicating increased water clarity. Four Coastal Management Zones were characterized by marine traffic as high traffic areas (HTAs) and two as low traffic areas (LTAs). Monthly composites for two periods, 2002–2019 (baseline) and 2020 were examined for K d (490). For months prior to the COVID-19 shutdown in Belize, there was generally no significant difference in K d (490) ( p > 0.05) between 2020 and baseline period in HTAs and LTAs. Through the shutdown, K d was lower in 2020 at HTAs, but not for LTAs. At the LTAs, the K d (490)s observed in 2020 were similar to previous years through October. In November, an unusually active hurricane season in 2020 was associated with decreased water clarity along the entire coast of Belize. This study provides proof of concept that satellite-based monitoring of water quality can complement in situ data and provide evidence of significant water quality improvements due to the COVID-19 shutdown, likely due to reduced marine traffic. However, these improvements were no longer observed following an active hurricane season.

Carbon on the Northwest European Shelf: Contemporary Budget and Future Influences - Oliver Legge; Martin Johnson; Natalie Hicks; Tim Jickells; Markus Diesing; John Aldridge; Julian Andrews; Yuri Artioli; Dorothee C. E. Bakker; Michael T. Burrows; Nealy Carr; Gemma Cripps; et al. (Frontiers in Marine Science, 2020)